The aesthetic Dimension of Lighting in the Academic Theatrical Show: اسيل ليث احمد-ثامر شوكت عبد الستار (Al-Academy, 2020)
The theatrical show depends in its formation on the technical system and the elements that it has for the theatrical show, and among these techniques is the lighting, where every director looked for a style and method of implementing them and giving aesthetic functions and characteristics that give the theatrical show an aesthetic and interpretive dimension, and that is through multiple expressions and connotations of the lighting in giving the show a functional and aesthetic character. Therefore, light has been shed on the lighting and its action in the theatrical show, due to its significant role in the modern theatrical shows. The current research, thus, has been divided into four chapters. The first chapter included the research problem which is presented in the form of the following question (identifying the aesthetic dimension of lighting in the academic theatrical shows). The first chapter included a presentation of the importance of the research, which is to benefit everyone who works in lighting specialty, and the study objective which concerns (revealing the aesthetic dimension of the lighting in the academic theatrical shows). As for the research limits, they are defined temporally by the period 2018, and spatially in Baghdad (Jassim Al-Aboudi Theatre). Then the terms mentioned in the research have been specified. The second chapter consists of two sections, the first section is a historical study of the lighting. The second section is a study of the academic theatre. The chapter concluded with the most important indicators of the theoretical framework as follows: 1- The lighting is considered a means that helps in defining shapes and create the aesthetic and expressive dimension for spectator's eyes. 2- The Iraqi theatre presented a group of thoughtful educational shows in the academic institutions. The third chapter included the research procedures, and sample represented by the play (C'est la vie Shakespeare) directed by (dr. Rasel Kadhim). As for the fourth chapter, it included the most important results of the research including:1- Through his design, the designer achieved harmony between the lighting and the technical elements of the show. 2- The lighting designer resorted to employing special lighting devices that help give an artistic and aesthetic dimension for the theatrical show. The research ended with a list of resources and references in addition to an abstract in English.